PENGARUH RESIDU BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG PANJANG (Vigna sinensis L.) - Safuan, La Ode; Buludin, Buludin; Suliartini, Ni Wayan Sri (Jurnal Agroteknos, 2012)
ABSTRACT The aim of the research was to study the effect of organic matter residue on the growth and production of long bean. This research was conducted at the Rahandouna Subdistrict, Kendari District, Southeast Sulawesi Province from March to June 2010. The research was prepared in randomized block design consisted of four levels: without organic matter (B0), residue of organic matter application at 5 ton ha-1 (B1), residue of organic matter application at 10 ton ha-1 (B2), and residue of organic matter application 15 ton ha-1 (B3). The variables observed were plant height, leaf number, leaf area, pod length, pod number, dan pod fresh weight. Analysis of variance (ANOVA) was used to analyze statistical data. Duncan's Multiple Range Test (DMRT) was applied to determine the significant difference among treatments at 95% confident level. The results of the research showed that, (1) The Residue of organic matter15 ton ha-1 partially had an effect on leaf area, leaf number, plant height, pod length, pod fresh weight., (2) The Residue of organic matter 15 ton ha-1 partially had an effect on increased pod length, pod number, and pod fresh weight of long bean. Key Words : Effect, Residual, Organic Matter